Translation Competence of Students and Its Implications for the Development of Syllabus/RPS in the Translation Course at the English Education Department of Sultan Amai State Islamic Institute (IAIN) Gorontalo - Pakaja, Marina; Bouti, Suleman; Lihawa, Kartin; Napu, Novriyanto (Universitas Negeri Gorontalo, 2025)
This study investigates the translation competence of students in the English Education Program at IAIN Sultan Amai Gorontalo and examines its implications for the development of the Translation course syllabus. Translation plays a critical role in education by bridging theoretical understanding and practical application, yet students often struggle with linguistic and cultural accuracy. Employing a mixed methods sequential explanatory design, the study was conducted in two phases. The first phase involved the quantitative analysis of students’ translation errors from the textbook Factfulness, focusing on morphological, syntactic, semantic, and cultural aspects. The second phase involved qualitative interviews to explore students’ translation strategies and cognitive processes. The findings revealed 285 translation errors, with semantic (121) and syntactic (78) errors being the most prevalent. Morphological (58) and cultural (28) errors were also significant, indicating challenges in structural adaptation and intercultural mediation. The qualitative data further highlighted students’ reliance on literal translation and limited metalinguistic awareness. These results underscore the need to reformulate the Translation course syllabus to emphasize dynamic equivalence, cultural competence, and contextual meaning. Recommendations include integrating process-based translation instruction, error analysis, and reflective translation practice to enhance pedagogical effectiveness.